Performance of reversible timber connections in Australian light timber framed panelised construction. (1st December 2022) - Yan, Zidi; Ottenhaus, Lisa-Mareike; Leardini, Paola; Jockwer, Robert
Abstract: This paper provides a novel insight into using reversible mass timber connectors in light-timber framed (LTF) construction to create dismountable, panelised LTF construction systems that enable adaptable building design and panel reuse in the context of a circular economy. The study presented in this paper focused on Australian LTF panelised construction:. A total of 10 IdeFix 304 connectors by SIHGA GmbH, and 20 M20 connectors by SHERPA Connection Systems GmbH were installed in Australian machine graded pine and subjected to monotonic tensile and shear loads to assess their feasibility in the given application. Two strength prediction models were evaluated in comparison to experimental results: Formulae given in the manufacturers' European Technical Assessments (ETAs) and a prediction model adapted from literature. On average, the latter was more accurate in the given configuration. Considering the set goal of repeated assembly and disassembly, the connectors with a tight fit faced tolerance issues due to moisture fluctuations. Furthermore, rupture of the connector was observed in some instances, owed to higher screw withdrawal capacity in Australian timber. A reduction of the number of screws or their length is suggested to achieve a more ductile response with screw withdrawal. Finally, following comparative analysis of experimental tests and prediction models, recommendations were made for future design of novel LTF panel connectors in the context of disassembly and reuse. Highlights: Two proprietary European connectors developed for mass timber construction were tested in Australia machine graded pine. A new modified prediction model for estimating the strength of the steel-timber connection was developed. The potential responses for compound angle screws were theoretically analysed. Timber connector design recommendations were made to allow for panel disassembly and reuse.